1997
DOI: 10.1046/j.1365-2672.1997.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of biodegradation of insoluble compounds by continuous determination of oxygen consumption

Abstract: Continuous determination of oxygen consumption by electrolytic respirometry has been experimented as a means to study the biodegradation kinetics of scarcely soluble environmental pollutants. The substrates used were the polycyclic aromatic hydrocarbons (PAH), naphthalene, phenanthrene, anthracene, fluoranthene and pyrene. The definition of an appropriate mode of PAH supply, either as crystals or more generally as a solution in a water non-miscible solvent, was found essential for yielding reproducible biodegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The critical issue here is that the substrate does not mix into the bulk solution, and thus, elevated concentrations can exist in this environment. Direct uptake of chemicals by bacteria at the aqueous phase/nonaqueous phase liquid interface has been demonstrated for hexadecane (8,9,17,23), pyrene (7), naphthalene (6,17,68), and fluoranthene (7). In soils, sorbed pesticides are initially held predominately on organic matter surfaces of soil particles.…”
Section: Discussionmentioning
confidence: 99%
“…The critical issue here is that the substrate does not mix into the bulk solution, and thus, elevated concentrations can exist in this environment. Direct uptake of chemicals by bacteria at the aqueous phase/nonaqueous phase liquid interface has been demonstrated for hexadecane (8,9,17,23), pyrene (7), naphthalene (6,17,68), and fluoranthene (7). In soils, sorbed pesticides are initially held predominately on organic matter surfaces of soil particles.…”
Section: Discussionmentioning
confidence: 99%
“…Time courses of oxygen uptake during degradation were recorded in respirometric flasks. Continuous monitoring of oxygen consumption is well suited to kinetic studies in heterogeneous media as oxygen consumed was shown to be proportional to the substrate consumed and to the biomass produced (Bouchez et al, 1997a). The experimentation covered a range of conditions, as presented in Table 2.…”
Section: Kinetic Study Of Growth Of Flocculating Strains On Hexadecanementioning
confidence: 99%
“…Time courses of oxygen consumed during growth on C "' were recorded using a sensitive respirometer (D12-S Sapromat, Voith) consisting of 12 conical flasks (500 ml) placed in a water bath maintained at 30 mC (Bouchez et al, 1997a). Determination of electrolytically produced oxygen supplied to the cultures at constant pressure allowed quasi-continuous recording of oxygen consumption.…”
Section: Cultures In Flasksmentioning
confidence: 99%
“…The flasks with leachate water were incubated in a water bath in a Voith Sapromat respirometer (Voith, Heldenheim/Brenz, Gemany) [30]. The Voith Sapromat continuously measure consumption of oxygen in solutions and the developed CO 2 gas in the flask is trapped with NaOH (Merck).…”
Section: Aerobic Treatment Experimentsmentioning
confidence: 99%